Cryptor currency, cryptor asset and fiat money: a critical appraisal from the shari’ah perspective - Adam Sa'ad, Auwal; Hasan, Aznan (2020)
The recent developments on crypto currency and crypto assets and also tokenisation activities has triggered a very important question of what actually is the “crypto” could it be regarded as asset or currency, and what’s the techniques for crypto valuation and how to assess the tokens and the digital assets what could be the connecting factor between the crypto and the current fiat money in our disposal, and lastly what should be the Shari’ah position on the matter.